Thermal oil aging behavior of hydrogenated nitrile butadiene rubber/multi-walled carbon nanotube composites under free or compression state. (August 2018) - Guo, Jianhua; Chen, Xuming; Li, Zhicai
The effect of the aging time on the thermal oil aging behavior of hydrogenated nitrile butadiene rubber (HNBR)/multi-walled carbon nanotube (MWCNT) composites under the free or compression state was investigated. The composites aged under the free state and the IRM 903 oil after aging for different time were characterized by Fourier transform infrared spectroscopy (FTIR) analysis. The surface morphology of the composites aged under the free state was characterized by microscopic analysis. The thermal stability of the composites aged for different time and the edge and inner samples obtained from the composites aged under the free or compression state were characterized by thermal gravimetric analysis. The effect of aging time on the compressive stress and compressive stain energy density of the compressed composites was investigated. The scanning electron microscopy and energy-dispersive X-ray spectroscopy analysis were exercised to the edge and inner samples obtained from the composites. This research facilitates to discover the heterogeneous aging effect on the degradation behavior of HNBR seals under the compression state in the hot oil environment.